The Influence of Social Media and Peer Pressure on Teenagers' Views and Behaviour Towards Vaping - Panjaya, Kyara Carol (Lembaga Pengembangan Kinerja Dosen, 2026)
Vaping is when you inhale a mist through a power based device, filled with flavourings, chemicals, and nicotine (Texas Health and Human Services, nd). Teenagers tend to vape due to external influences such as advertisements and social interactions, which has a significant contribution in the role of gaining societal acceptance of vaping amongst teenagers (CDC, nd). However its use in teenagers is illegal as per the Indonesian Government Regulation Number 109 2012, which restricts individuals below 18 years old from vaping. A study conducted in 2018 has reported that teenagers have started vaping from 2017. Despite rules and regulations, teenagers are still able to access it which makes the law enforcement ineffective that leads to teenagers being able to have access to vapes. This research will investigate the influence of social media and peer pressure on underage vaping, focusing on how contents on social media, their peers along with social interactions shape the perspective and behaviour of a teenager towards vaping. This following topic is important as social media plays a significant role in the normalisation of vaping despite harmful effects. It aims to recognize how social media and interactions among fellow peers influence a teenager. With the use of qualitative and quantitative methods such as surveys and interviews, it will also apply theories from 3 thinkers to have a better understanding of a teenager’s decision.